نمــوذج مقترح لتطوير البطاقة التموينية بأستخـــدام التوزيع الحساس لوحدات المنفعة المستهدفة في العراق (المجلة العراقية للعلوم الاقتصادية, 2018)
The food card is approach to support purchasing power individuals , that the consumer will receive quantities of foods in order To help them to rise their welfare.The concept of this system contain another variables which related to this system ,as the age distribution and gender-distribution and the functional distribution and the income, official distribution income distribution.there for system may be increase the purchasing power for our consumer.